Risk factors for peripheral neuropathy in patients with diabetes mellitus - Akter, Taslima; Akhter, Qazi Shamima; Polly, Zinat Ara; Debsarma, Smita (IMC Journal of Medical Science, 2020)
Background and Objectives: Peripheral neuropathy is a complication of diabetes mellitus (DM). Several risk factors may accelerate the development of peripheral neuropathy in DM. The objective of the current study was to determine the risk factors for development of peripheral neuropathy in patients with DM. Methods: The study was conducted from July 2014 to June 2015 in a large hospital of Dhaka city. A total of 150 diabetic patients of both sexes with and without peripheral neuropathy were enrolled. The investigations included interviewing on clinical history, anthropometry (height, weight, waist- and hip-circumference), blood pressure measurement, estimation of HbA1c, fasting blood glucose and lipids. Results: Duration of diabetes for more than 5 years was significantly (χ2=124.39, p <0.001) associated with peripheral neuropathy. Sequential logistic regression analysis revealed high BMI (> 25 Kg/m2; OR=8.8, p <0.001), HbA1c (>6.5%; OR=5.25, p<0.05) and higher total cholesterol level (> 200 mg/dl; OR=4.74, p <0.05) as the significant risk factors for peripheral neuropathy. Conclusion: Obesity, hyperglycemia and high total cholesterol were possible risk factors for development of diabetic peripheral neuropathy. Proper glycemic control and prevention of obesity and dyslipidemia could be helpful to avert progression to peripheral neuropathy in diabetic population. Ibrahim Med. Coll. J. 2019; 13(2): 40-44